The Development of Jathilan Performance as an Adaptive Strategy Used by Javanese Farmers - Irianto, Agus Maladi (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2016)
This paper is aimed at describing adaptive strategy used by supported community to preserve and develop Jathilan, Javanese traditional ritual art performance. In describing the aim, the most fundamental nature and meaning attached in the artistic performance had been studied. Qualitative method was employed through literature review and field study. This study located in Magelang Regency, Central Java. The Jathilan in this paper is seen as cultural identity for its supported community, that has a specific role socially and ritually. The supported community, in addition, believes that this traditional art is not only acted as an entertainment, but also a facilitator for their hopes and prays. Despite some changes have influenced the differences of style and variation in the performing art, however, the changes themselves are the manifestation of adaptive strategy had from the supported community to preserve and conserve Jathilan performing art.